Successful implementation of parenting support at preschool: An evaluation of Triple P in Sweden - Anton Dahlberg; Raziye Salari; Karin Fängström; Helena Fabian; Anna Sarkadi (PLoS ONE, 2022)
Although emotional and behavioural problems among young children are common and, if unaddressed, can lead to multi-facetted problems later in life, there is little research investigating the implementation of parenting programs that target these problems. In this study, the RE-AIM framework was used to evaluate the implementation of the Triple P parenting program in a preschool setting at a medium-sized municipality in Sweden. Reach increased over time, showing an overall increase in participating fathers and parents with lower education. Effectiveness outcomes showed an improvement in emotional and behavioural problems in children and less mental health-related symptoms and higher self-efficacy in parents. Adoption rate was 93.3%. To ensure staff “buy-in”, designated coordinators made changes in recruitment procedures, and provided supervision and training to all Triple P practitioners. Implementation adaptations were made, such as minor revisions of parenting strategies and other program content, as well as providing child care during seminars and groups, and setting up weekend-groups. Maintenance assessed through 12 month follow-up data suggested that several child and parent outcomes were maintained over time. Uppsala municipality continues to offer Triple P to parents. The reach, effectiveness, adoption, implementation and maintenance of the program were all satisfactory and demonstrated the suitability of delivering evidence-based parenting support using preschools as an arena.